Cuantificación de carbono en biomasa aérea y necromasa en zonas quemadas dentro de la Reserva Ecológica Los Ilinizas - Noboa Egas, Saúl Alejandro (2016)
This research was conducted in the moorland of the Ecological Reserve Illinizas (REI), specifically in areas burned during the last 5 years. The location of these areas was provided by the administrative area of the reserve. The purpose of the research was to quantify the carbon in the air biomass and necromass in burned areas of REI and correlate with the time elapsed after the fire, in order to determine the age of the fire. Also, knowing the vegetation that would be lost in case of a fire, its carbon content and the CO2 emissions that would produce to the atmosphere after being burned. The result was an equation which could estimate the time that has elapsed after the fire knowing the carbon contained in biomass moorland. Regarding to the accumulated biomass and carbón, was obtained that from 4 to 5 years after the fire exist approximate 24 ton biomass / ha and 7.57 ton C / ha. It´s important to mention that wasn´t found necromass in the study area. Regarding CO2 emissions, this will depend on the amount of biomass. Assuming for example the largest extension of the studied areas (850 ha in August 2015) the estimated amount of CO2 would be 23,593 ton CO2.